Mrs. lincoln's rival ebook A novel. - Chiaverini, Jennifer (2014)
The New York Times bestselling author of Mrs. Lincoln’s Dressmaker and Canary Girls reveals Mary Todd Lincoln’s very public social and political contest with Kate Chase Sprague in this astute and lively novel of the politics of state—set against the backdrop of Civil War Era Washington. Beautiful, intelligent, regal, and entrancing, young Kate Chase Sprague stepped into the role of establishing her thrice-widowed father, Salmon P. Chase, in Washington society as a Lincoln cabinet member and as a future presidential candidate. For her efforts, The Washington Star declared her “the most brilliant woman of her day. None outshone her.” None, that is, but Mary Todd Lincoln. Though Mrs. Lincoln and her young rival held much in common—political acumen, love of country, and a resolute determination to help the men they loved achieve greatness—they could never be friends, for the success of one could come only at the expense of the other...